Perspektif pembeli rumah berpendapatan rendah mengenai kebolehdiaman di Shah Alam Selangor - Zulkepli, Mohd Farhan; Hashim, Ahmad Hariza; Abu Samah, Asnarulkhadi; Redzuan, Ma'rof (Persatuan Ekonomi Pengguna dan Keluarga Malaysia (MACFEA), 2012)
The purpose of this study to examine the level of residential importance perception among residence of apartment at Section 27 Shah Alam Low Cost Apartment. The objectives were to identify about physical and safety dimension as predictor in livability dimension. A total of 400 respondents were selected to participate in this study by using systematic sampling. Data have collected by interviewing respondents using questionnaires Likerts Scale measurement was used to determine the level of residential needed perception. Data were processed using a Statistical Package for the Social Science (SPSS) program and use Multiple Regression to test the hypothesis. The result showed that physical and safety aspect have been given priority by the respondents in determining the level of housing perception among resident Section 27 Shah Alam low cost apartment. The result showed that physical and safety dimension have a contribution towards social dimension perception This research will give implications to buyers, housing developers and governments. They will get some inputs from residents in term of housing perception on physical dimension and safety needed by them which mean the developers should considered the physical and safety dimension as priority before they can consider for the social dimension.